Just urban transitions: Toward a research agenda. (19th February 2020) - Hughes, Sara; Hoffmann, Matthew
Abstract: While there are excellent policy and academic foundations for thinking about and making sense of urban climate action and questions of justice and climate change independently, there is less work that considers their intersection. The nature and dynamics of, and requirements for, a just urban transition (JUT)—the fusion of climate action and justice concerns at the urban scale—are not well understood. In this review article we seek to rectify this by first examining the different strains of justice scholarship (environmental, energy, climate, urban) that are informing and should inform JUT. We then turn to a discussion of just transitions in general, tracing the history of the term and current understandings in the literature. These two explorations provide a foundation for considering both scholarly and policy‐relevant JUT agendas. We identify what is still needed to know in order to recognize, study, and foster JUT. This article is categorized under: The Carbon Economy and Climate Mitigation > Benefits of Mitigation Climate, Nature, and Ethics > Climate Change and Global Justice Abstract : Just urban transitions research and policy agendas center alternative urban futures: cities where the distribution of environmental risks and benefits do not disproportionately burden marginalized groups; where decision‐making is transparent, engaged, and democratic; and where policies seek to remedy structural inequalities and prior injustices.